Parent-based self-medication in Pakistani children: a qualitative cross-sectional survey - Solangi, Muhammad Aslam; Ali, Muhammad; Mushtaq, Daniyal; Zaid, Muhammad; Riaz, Muhammad; Nasir, Ali (Bangladesh Journal of Medical Science, 2016)
Background: A large percent of the population in developing countries is comprised of children. Drug utilization patterns in children is of great concern universally and has gained a lot of attention. Objectives: The aim of this study was to test the Pakistani parents knowledge, attitudes and practice (KAP) towards self-medicating their children. Methods: A cross-sectional study was designed and the data collection was carried out in several government and private hospitals in Karachi, Pakistan. Non probability convenient random sampling method was employed to select the participants. Results: In our study, 45 (44.55%) parents were university graduates. The most frequent medicines used were Panadol (paracetamol) 84 (83%). The most common self-treated symptom was cough & cold 73 (72.27%). In case of self-treatment failure most of the parents in the present study tend to consult general practitioners in private clinics 62 (61%), while 31 (31%) of them seek advice from child specialists in hospitals. Doctors were the first favourite source for 92 (91.0%) of parents. The most common reasons were the expensive consultation fees and long waiting time in the clinics. A large portion of parents disagreed that health care workers attitudes were bad, or that information relayed to them was insufficient. Another important finding was 52 (51.4%) of parents were convinced that they can diagnose their childs illnesses by the symptoms. Conclusions: The study uncovered that parents knowledge was lacking, and their parental self-medication practice demonstrated to be unseemly. Based on the results of our study, we conclude that there is a critical need of appropriate interventions to tackle this issue. Bangladesh Journal of Medical Science Vol.15(1) 2016 p.33-38